Taking a hit to save the world? Employee participation in a corporate social initiative. (5th February 2018) - Bode, Christiane; Singh, Jasjit
Abstract : Research Summary: Companies often justify their corporate social initiatives by citing talent management benefits. We examine the extent of, and the reasons for, employee interest in such an initiative in a global management consulting firm. We find a large fraction of employees to be interested in participation in the initiative even when participation requires a personal sacrifice in the form of a salary cut. However, this interest is driven not just by prosocial motivation: Expectations regarding private benefits, such as improved career prospects from new skills acquired, also play a role. Considerations of social impact and private benefits are equally salient when no salary cut is required, but private considerations become more prominent when participating employees are asked to accept a salary cut. Managerial Summary: Many companies are moving from stand‐alone corporate social responsibility (CSR) projects to social initiatives integrated into strategy. Providing employees with the opportunity to participate in such initiatives is said to help attract, motivate and retain talent. In this study, carried out in collaboration with a management consulting firm, we examine how much and why employees value participation in a corporate social initiative. Based on interviews and survey data, we find that employees are not only interested in, but often even willing to accept, a temporary salary cut for the opportunity. However, altruistic motivation is not the only driver of this interest: Employees also expect and value the possibility that the experience would lead to private benefits, such as developing skills likely to enhance their career prospects.